Assessing the Effectiveness of Coastal Marine Protected Area Management: Four Learned Lessons for Science Uptake and Upscaling - Pelletier, Dominique (Frontiers in Marine Science, 2020)
For almost two decades, marine protected areas (MPAs) have been a central instrument of coastal conservation and management policies, but concerns about their abilities to meet conservation goals have grown as the number and sizes of MPAs have dramatically increased. This paper describes how a large (15 year) program of transdisciplinary research was used to successfully measure MPA management effectiveness (ME) - how well an MPA is managed, how well it is protecting values, and how well it is achieving the various goals and objectives for which it was created. This paper addresses the coproduction and uptake of monitoring-based evidence for assessing ME in coastal MPAs by synthesizing the experiences of this program conducted with MPA managers. I present the main outcomes of the program, many were novel, and discuss four ingredients (learned lessons) that underpinned the successful uptake of science during and after the research program: (i) early and inclusive co-design of the project with MPA partners and scientists from all disciplines; (ii) co-construction of common references transcending the boundaries of disciplines, and standardized methodologies and tools; (iii) focus on outcomes that are management-oriented and understandable by end-users; and (iv) ensuring that capacity building and dissemination activities occurred during and persisted beyond the program. Standardized monitoring protocols and data management procedures, a user-friendly interface for indicator analysis, and dashboards of indicators related to biodiversity, uses and governance, were the most valued practical outcomes. Seventy-five students were trained during the projects and most of the monitoring work was conducted with MPA rangers. Such outcomes were made possible by the extended timeline offered by the three successive projects. MPA managers’ and scientists a posteriori perceptions strongly supported the relevance of such collaboration. Local monitoring and assessment meets the needs of MPA managers and forms the basis for large-scale assessments through upscaling. A long-term synergistic transdisciplinary collaboration between coastal MPA managers and research into social-ecological systems (SESs) would simultaneously i) address the lack of long-term resources for coastal monitoring and SES-oriented research; ii) increase science uptake by coastal managers, and iii) benefit assessments at higher levels or at broader geographic scales.